The competency index for clinical research professionals: a potential tool for competency-based clinical research academic program evaluation - Jones, Carolynn Thomas; Liu, Xin; Hornung, Carlton A.; Fritter, Jessica; Neidecker, Marjorie V. (Frontiers in Medicine, 2024)
Background: Accreditation of graduate academic programs in clinical research requires demonstration of program achievement of Joint Task Force for Clinical Trial Competence-based standards. Evaluation of graduate programs include enrollment, student grades, skills-based outcomes, and completion rates, in addition to other measures. Standardized measures of competence would be useful. Methods: We used the Competency Index for Clinical Research Professionals (CICRP), in a separate-sample pretest-posttest study to measure self-confidence or self-efficacy in clinical research competency comparing cohorts of students entering and completing a master’s degree program in clinical research across three semesters (summer 2021 – spring 2022). CICRP is a 20-item Likert scale questionnaire (0= Not at all confident; 10=extremely confident). Results: The study sample of 110 students (54 in the entry course, 56 in the exit course) showed overall 80.9% entered the program with only a baccalaureate degree and 55.5% had no prior experience in managing clinical trial research. Cronbach alpha for the instrument showed a high level of content validity (range 0.93 to 0.98). Median CICRP item rating range at entry was [1, 6] and at exit [7, 10]. Mean CICRP total score (sum of 20 items) at entry was 72.7 (SD 41.9) vs. 167.0 (SD 21.1) at exit (p < 0.001). Mean total score at program entry increased with increasing years of clinical trial management experience but attenuated at program exit. Conclusion: This is the first use of the CICRP for academic program evaluation. The CICRP may be a useful tool for competency-based academic program evaluation, in addition to other measures of program excellence.